2017
DOI: 10.3233/wor-172581
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress and role of personality in a sample of Italian bus drivers

Abstract: An integrated method, considering both objective and subjective indicators, seems adequate to evaluate work-related stress in professional drivers. Personality traits are relevant in determining perception of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Besides the missing individuals, the years considered in the research (2012–2014) are the years of the world economic crisis, which may affect the likelihood of migrant workers perceiving insufficient individual work demand [40,41,42,43] and experiencing salary reductions [44,45,46], which increase the presence of depressive symptoms. However, in China, the economic crisis was not as significant as in other parts of the world, especially for migrant workers from rural areas, because migrant workers can return to rural areas if they cannot find a suitable job in an urban area [47].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the missing individuals, the years considered in the research (2012–2014) are the years of the world economic crisis, which may affect the likelihood of migrant workers perceiving insufficient individual work demand [40,41,42,43] and experiencing salary reductions [44,45,46], which increase the presence of depressive symptoms. However, in China, the economic crisis was not as significant as in other parts of the world, especially for migrant workers from rural areas, because migrant workers can return to rural areas if they cannot find a suitable job in an urban area [47].…”
Section: Discussionmentioning
confidence: 99%
“…As our study included participants with different organizational levels, the OWI could be influenced by their specific roles as employees or owners, for instance. Secondly, employees’ personality traits and attitudes or behaviors can influence their job demands perceptions and performance, as other studies suggested [62]. Thirdly, while it has been mainly considered that stress and job demands could negatively affect employees’ health status, more recently it has also been suggested that work can positively affect workers’ well-being by improving cognitive functioning and perceived health [63].…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of stress as a pathogenetic factor of various psychosomatic illnesses has been recognized ever since the first half of the last century, it is only in these last decades that the deepening of knowledge in the fields of neurochemistry, neuroendocrinology, and immunology has allowed us to understand and interpret, in large, the variations of the specific mechanisms that are at the basis of pathologies induced by an excess of adverse stimuli [4,5].…”
Section: Introductionmentioning
confidence: 99%